"In the flesh": Narratives of family caregivers at risk of Early-onset Familial Alzheimer's Disease. (July 2020) - García-Toro, Maritza; Sánchez-Gómez, María Cruz; Madrigal Zapata, Lucía; Lopera, Francisco Javier
In the growing body of literature dealing with the consequences of family caregiving amongst people with dementia, there are few studies examining the impact of Early-onset Familial Alzheimer's Disease on caregivers. This study exposes the subjective experience of a group of family caregivers who themselves possess a genetic susceptibility to develop this form of dementia. We interviewed and analyzed the accounts of 27 caregivers belonging to family lineages carrying the E280A mutation for Early-onset Alzheimer's Disease. We utilized a phenomenological method to analyze these accounts, initially tracking seven theoretical categories (Anxiety, Depression, Burden, Resilience, Self-efficacy, Social Support, and Coping Strategies) and then subsequently two additional categories which emerged (Conceptions about the Disease and Other Vital Experiences Interfering with Caregiving). The results show that caring for a loved one while simultaneously running the risk of developing the same form of Alzheimer's Disease permeates the caregivers' experience both in a negative and a positive way. The continuous exposition to emotional stress in these caregivers should be seriously considered as they may be at risk of accelerating the onset of symptoms of Alzheimer's Disease, while simultaneously, early psychological symptoms of dementia may be masked by the emotional sequelae of caregiving, interfering with early diagnosis. Certainly, support services for the entire family group are suggested.